Dobór miar do systemów pomiaru efektywności organizacyjnej : dylematy i propozycje rozwiązań - Dyduch, Wojciech (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper presents the problems concerning the contemporary approaches towards building integrated performance measurement and management systems (PMMS). First, the dilemmas of choosing the right measures are described, including the choice between subjective and objective measures, as well as financial and non-financial ones. Next, the principles of designing the performance measurement and management systems are described as well as new propositions are given. Corporate entrepreneurship is proposed for inclusion in designing the PMMS. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 68-77